Central TYK2 inhibition identifies TYK2 as a key neuroimmune modulator - Tyler P. Molitor; Genki Hayashi; Mei-Yao Lin; Carissa J. Dunn; Nathan G. Peterson; Robert G. Poston; Michael P. Kurnellas; David A. Traver; Seona Patel; Zeynep Akgungor; Virginia Leonardi; Colizel Lewis; et al. (Proceedings of the National Academy of Sciences, 2025)
GWAS have identified tyrosine kinase 2 (TYK2) variants in multiple inflammatory disorders, specifically a protective hypomorphic TYK2 allele (P1104A) in multiple sclerosis (MS). Impaired TYK2 signaling within the central nervous system (CNS) may impart the protective effects of TYK2 P1104A allele in MS. We deployed brain-penetrant TYK2 inhibitors (cTYK2i) alongside the peripherally restricted TYK2 inhibitor (pTYK2i; BMS-986165) to untangle the contributions of central TYK2 inhibition in diverse models of neuroinflammation. While pTYK2i had little impact, cTYK2i reduced clinical score, lymphoid cell infiltration, and cytokines/chemokines in experimental autoimmune encephalomyelitis (EAE). Microglial activation was attenuated in cTYK2i-treated EAE spinal cords and circulating neurofilament light (NfL) was reduced in plasma and cerebral spinal fluid (CSF). Additionally, cTYK2i was protective in an antibody-mediated mouse model of primary progressive MS (PPMS). Finally, we demonstrate TYK2 inhibition has a robust impact on a unique subset of activated astrocytes termed Interferon-Responsive-Reactive-Astrocytes (IRRA). The data presented herein identify a key role for CNS TYK2 signaling in regulating neuroinflammation and solidify TYK2 as a potential therapeutic target for MS.